Optimization of an improved intermodal transit model equipped with feeder bus and railway systems using metaheuristics approaches - Almasi, M.H.; Sadollah, A.; Kang, S.; Karim, M.R. (MDPI, 2016)
One of the serious concerns in network design is creating an efficient and appropriate network capable of efficiently migrating the passenger's mode of transportation from private to public. The main goal of this study is to present an improved model for combining the feeder bus network design system and the railway transit system while minimizing total cost. In this study, the imperialist competitive algorithm (ICA) and the water cycle algorithm (WCA) were employed to optimize feeder bus and railway services. The case study and input data were based on a real transit network in Petaling Jaya, Kuala Lumpur, Malaysia. Numerical results for the proposed model, including the optimal solution, statistical optimization results and the convergence rate, as well as comparisons are discussed in detail.